Cigarette smoking among those with mental disorders in the US population: 2012–2013 update. Issue 1 (30th October 2018) - Smith, Philip H; Chhipa, Mohammad; Bystrik, Josef; Roy, Jordan; Goodwin, Renee D; McKee, Sherry A
Abstract : Background: Recent nationally representative estimates from the USA suggest the prevalence of cigarette smoking continues to be much higher among those with mental disorders compared with those without; however, prevalence estimates for current cigarette use by specific diagnoses are outdated. Methods: We analysed data from the National Epidemiologic Survey on Alcohol and Related Conditions III (2012–2013). We estimated the prevalence of lifetime and past-year smoking, lifetime and past-year daily smoking, and lifetime smoking cessation among ever smokers (ie, the quit ratio) among those with common mood, anxiety and substance use disorders in comparison to those without these disorders. Results: Across disorders, smoking prevalence was higher and the quit ratio was lower among those with common mental disorders compared with those without, with twofold to sixfold relativedifferences in the odds of the magnitude. Conclusions: Despite tobacco control advances since 2000 and resulting declines in smoking prevalence, smoking remains extraordinarily more common among those with mood, anxiety and substance use disorders, with highest rates among those with bipolar and substance use disorders.